Analisis Variable Costing dan Harga Pokok Proses pada UMKM Daur Ulang Ban Bekas: Analysis of Variable Costing and Cost of Process in MSMEs Recycling Used Tires - Meilani Putri; Tsania El-Ihza Imtithal; Lira Lady Diana Simanjuntak; Kholida Atiyatul Maula (CV Warnak Johanna Nusantara, 2026)
this study aims to analyze the application of Variable Costing and process cost methods at Lantar Bun, an SME engaged in recycling container tires in Bekasi Regency that produces sofa rubber for the Taiwanese export market. Using a descriptive quantitative with a case study approach, data were collected through in-depth interviews and documentation. The results show that Variable Costing yields a cost of production of IDR 5,500 per kilogram, lower than full costing at IDR 5,672.92 per kilogram, as fixed costs are not allocated to products. The application of process costing across for production departments reveals cost accumulation from IDR 4,396.35 per kilogram in the Cutting Departments to IDR 5,585.42 per kilogram in the Reduction Department. Profitability analysis indicates a contribution. The integration of both methods proves to produce more comprehensive and relevant cost information for managerial decision-making compared to the estimation method previously used.